An inner city preschool visual screening programme: long term visual results. Issue 5 (1st May 1998) - Bowman, R J C; Williamson, T H; Andrews, R G L; Aitchison, T C; Dutton, G N
Abstract : AIMS: The aim of this study was to investigate the long term outcome of the treatment of amblyopia as a sequel to preschool screening, which has not hitherto been described. METHODS: All patients originally referred from a preschool screening programme were recalled for examination by letter. 255 patients were reviewed at least 4 years after discharge of which 88 were definitely amblyopic at presentation and 107 were not amblyopic at presentation and were used as controls. RESULTS: 79% of the amblyopes improved or maintained visual acuity after discharge but this was reduced to 42% after an age induced increase (estimated from the controls) was compensated for. The mean drop in visual acuity in the amblyopic eyes which deteriorated was 0.23 (SD 0.15) logMAR units. Stepwise multiple linear regression showed that the best single predictor of post-discharge deterioration in visual acuity was the improvement in visual acuity seen during treatment ( R 2 = 19%). Eccentric fixation at time of follow up (increasing R 2 to 47%) and good presenting acuity (further raising R 2 to 57%) contributed additional information, and were both associated with greater post-discharge deterioration in visual acuity. CONCLUSIONS: The majority of amblyopes who attended for follow up maintained or improved their visual acuities after discharge. Those patients who demonstrated deterioration of their amblyopia had usually improved well during the programme and were often fixating eccentrically at follow up.